Spectroscopic and dynamic light scattering studies of the interaction between pterodontic acid and bovine serum albumin - Yunfang Li; Guangzhong Yang; Zhinan Mei (Elsevier, 2012)
Pterodontic acid (PA) has been isolated from Laggera pterodonta, a Chinese herbal medicine, and shown to possess antibacterial activity in vitro. To facilitate its preclinical development, the interaction between PA and bovine serum albumin (BSA) was studied using a fluorescence quenching technique, ultraviolet-visible spectrophotometry and dynamic light scattering (DLS). At temperatures of 297 K and 310 K and an excitation wavelength of 282 nm, the fluorescence intensity of BSA decreased significantly with increasing concentration of PA attributed to the formation of a PA-BSA complex. The apparent binding constant, number of binding sites and corresponding thermodynamic parameters were calculated and the main intermolecular attraction shown to result from hydrogen bonding and van der Waals forces. Synchronous fluorescence spectrometry revealed that the binding site in the complex approached the microenvironment of Trp and three-dimensional fluorescence spectroscopy showed the binding induced conformational changes in BSA. Using DLS, increasing PA concentration was shown to cause a gradual increase in hydrodynamic diameter and significant aggregation of the complex.